Soil porosity as a key factor of soil aggregate stability: insights from restricted grazing - Yang, Yi; Meng, Zhongju; Li, Haonian; Gao, Yue; Li, Tianyang; Qin, Lei (Frontiers in Environmental Science, 2025)
Overgrazing leads to steppe degradation and soil structure deterioration, which is common in desert steppes. Restricted grazing is a sustainable practice, but the mechanisms by which soil structure responds to restricted grazing have received little attention. This study examined the effects of two different grazing management strategies, namely, restricted grazing and free grazing (CK), on soil structure indicators in the desert steppe. The restricted grazing further included grazing exclusion (GE) and seasonal grazing (SG). Additionally, a preliminary exploration was conducted to identify the main factors affecting the soil aggregate stability. Our results demonstrated that GE significantly increased clay (<0.002 mm) and silt (0.002–0.02 mm) in the 0–10 cm and 10–20 cm layers by an average of 71.27% and 70.64%, respectively. Additionally, SG significantly increased clay (<0.002 mm), silt (0.002–0.02 mm), and macroaggregates (>0.25 mm) in the 0–10 cm layer. GE significantly increased soil organic carbon in the 0–10 cm and 10–20 cm layers by 7.02 g/kg and 7.45 g/kg, respectively. In addition, SG had no significant effect on soil organic carbon. The findings obtained from the computations using the boosted regression tree (BRT) demonstrated that, within the study period, soil porosity significantly affects soil aggregate stability compared to other factors. Moreover, it possessed an average explanatory power that surpassed 45%. Overall, the soil structure is better under GE than under SG, and GE is the key to improving the soil structure of desert steppe. The research will contribute to a more profound comprehension of the impact of grazing on soil structure. Therefore, it is recommended that grazing closures be prioritized in desert grasslands to promote coordination between grassland restoration and livestock development.